Correlation between Umbilical Cord Torsion and Doppler Parameters of the Umbilical Artery: A Single-Center Retrospective Case-Control Study - Yuan Li; Dirong Zhang; Yu Shi (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: Umbilical cord torsion is one of the known causes of perinatal fetal death, adding to the increase in perinatal morbidity and mortality. However, there is no study on the relationship between umbilical cord torsion and the changes in umbilical artery Doppler parameters. Methods: The subjects included 962 pregnant women who were discharged from our hospital from January 2015 to November 2021 and were eligible for inclusion (415 in the study group and 547 in the control group). The measurement data of umbilical artery Doppler parameters (peak systolic velocity (PSV), systolic/diastolic ratio (S/D), resistance index (RI), pulse index (PI)) were collected from 21 to 40 weeks of gestation, and the differences among the collected parameters were statistically analyzed. Results: The peak systolic velocity (PSV) of umbilical artery were positively correlated with gestational age, while the Doppler resistance parameters (S/D, RI, PI) of the umbilical artery were negatively correlated with gestational age. The mean values of umbilical artery Doppler parameters (PSV, S/D, RI, PI) in the study group were significantly lower than those in the control group at the same gestational age (p < 0.05). Conclusions: The decrease of Doppler parameters in the umbilical artery in late pregnancy was significantly related to umbilical cord torsion, which may be used as a reason for prenatal ultrasound screening for umbilical cord torsion. In the future, we need to combine further perinatal and prognostic data to carry out a prospective study.